Lithium tetrafluoroborate catalyzed highly efficient inter- and intramolecular aza-Michael addition with aromatic amines - Lad, Uday P.; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2011)
Lithium tetrafluoroborate has been demonstrated for the first time to be an efficient catalyst in intermolecular aza-Michael addition aromatic amines to electron deficient alkenes. Suitability of the same catalyst in intramolecular aza-Michael addition leading 2-aryl-2,3-dihydroquinolin-4(1H) ones has also been described. (C) 2011 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-aryl-2; 3-dihydroquinolin-(4H)-1-ones; Anilines; Lithium tetrafluoroborate; Michael addition

Practical and highly efficient protocol for multicomponent synthesis of beta-phosphonomalononitriles and 2-amino-4H-chromen-4-yl phosphonates using diethylamine as a novel organocatalyst - Kulkarni, M. A.; Pandurangi, V. R.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2012)
Diethylamine has been demonstrated for the first time to be a highly efficient organocatalyst in the solvent-free synthesis of beta-phosphonomalononitriles by a three component condensation of aldehyde, malononitrile and dialkyl phosphite at ambient temperature. The applicability of the same catalyst in the synthesis of diethyl (2-amino-3-cyano-chromene-4-yl) phosphonic acid esters has also been described. (c) 2012 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-amino-4H-chromenes; beta-phosphonomalononitriles; diethylamine; multicomponent reactions; organocatalyst; Phospha-Michael reaction

Diethylamine Dess-Martin periodinane: an efficient catalyst-oxidant combination in a sequential, one-pot synthesis of difficult to access 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Kupwade, Ravindra V.; Khot, Supriya; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2017)
Herein, diethylamine Dess–Martin periodinane has been demonstrated for the first time as an efficient catalyst–oxidant combination in a sequential, one-pot synthesis of medicinally privileged but difficult to access 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines via a pseudo-four component reaction between 2,6-disubstituted benzaldehydes, malononitrile, and thiols. Ambient reaction conditions, excellent yields, and total avoidance of conventional isolation as well as purification are the noteworthy merits of this developed protocol.